Effect of boiling temperature and time on total flavonoids, total phenols, and radical scavenging activity of decoction water fresh gotu kola (Centella asiatica (L.) Urb.) - Safrina, Devi; Susanti, Devi Yuni; Widodo, Harto (Proceedings of the International Conference on Green Technology; Vol 14 No 1 (2024): Proceeding of 14th International Conference on Green Technology, 2024)
Gotu kola (Centella asiatica (L.) Urb.) possesses significant pharmacological effects as a versatile herb, particularly in wound healing, neuroprotection, and cardiovascular health. Some people derive the benefits of medicinal plants by boiling and consuming them. The boiling process significantly impacts the biochemical composition, including total phenols, total flavonoids, and antioxidant activity. This study aims to investigate the impact of temperature and time on total flavonoids, total phenols, and radical scavenging activity during the boiling process of fresh C. asiatica. Three different temperature treatments (75°C, 85°C, 95°C) and four different boiling time treatments (5, 10, 15, and 20 minutes) were used to assess the total flavonoid content, total phenolics, and radical scavenging activity using the DPPH method. Quantitative data analysis employed DMRT and PCA techniques to ascertain the impact and correlation among factors. The results showed that temperature and boiling time significantly influenced total flavonoids, total phenols, and radical scavenging activity. Maximum levels of total flavonoids, total phenols, and radical scavenging activity were achieved in C. asiatica boiling water after boiling at 95 °C for 20 minutes. Temperature, total flavonoids, and total phenols have a strong correlation, where total flavonoids and total phenols increase as the boiling temperature increases.